2016
DOI: 10.1111/jpn.12555
|View full text |Cite
|
Sign up to set email alerts
|

Egg production performance, egg yolk antioxidant profile and excreta concentration of corticosterone in golden pheasants (Chrysolophus pictus) fed diets containing different levels of green vegetables

Abstract: In order to study the effect of feeding graded levels of green vegetables on egg production performance and egg yolk antioxidant status, 27 female golden pheasants (GP) were randomly distributed into three groups of nine each in an experiment based on completely randomized design. The diets of the birds in groups T , T and T contained 1.4%, 2.7% and 5.0% of green vegetables respectively. Feeding of experimental diets started on 12th February (day 1) and was continued till 30 June 2012. Average number of eggs l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
3
2
0
Order By: Relevance
“…In the present study, yolk color fan score was increased with commercial colorant supplement and spinach leaf supplements. Similar results were determined in green vegetable supplementation by Kullu et al (2017). Spinach leaf is a green vegetable and contains mostly lutein, moreover lutein bioavailability from lutein supplements, lutein of spinach did not differ.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, yolk color fan score was increased with commercial colorant supplement and spinach leaf supplements. Similar results were determined in green vegetable supplementation by Kullu et al (2017). Spinach leaf is a green vegetable and contains mostly lutein, moreover lutein bioavailability from lutein supplements, lutein of spinach did not differ.…”
Section: Resultssupporting
confidence: 83%
“…In the current experiment the results showed that supplementation of dried spinach leaf by 1% increased the egg mass. Similar results were observed in a study that supplementation of green vegetables (spinach and fenugreek) increased the egg mass and egg production in pheasants (Kullu et al, 2017). In other studies, different lutein sources supplementation had no effects on feed intake, live weight, egg mass and hen day production (Hasin et al 2006;Lokaewmanee et al, 2011;Lu et al 2013).…”
Section: Resultssupporting
confidence: 78%
“…No signi cant (p > 0.05) antioxidant activity of egg yolk or meat was found when measured in the above study with a ferric reduction antioxidant power assay. Similarly, in golden pheasants (Chrysolophus pictus) fed diets containing different levels of green vegetables, egg yolk total antioxidant activity was positively affected [77]. In the current study, organic Se was found to increase the carotenoid content and decreased cholesterol content of egg yolk, which may have led to the higher egg antioxidant capacity.…”
Section: Discussionsupporting
confidence: 50%
“…3.1 regarded as 'Least Concern' (2012). The previous studies on C. pictus mainly focused on possible evolutionary significance of egg-white proteins, egg production performance and nutritional value (Baker 1965;Gao et al 2016;Kullu et al 2017). Genetic characteristics are very important in species conservation, however, there is no more reports on the mitogenome of the golden-pheasant C. pictus in North China.…”
mentioning
confidence: 99%
“…2016 ; Kullu et al. 2017 ). Genetic characteristics are very important in species conservation, however, there is no more reports on the mitogenome of the golden-pheasant C. pictus in North China.…”
mentioning
confidence: 99%